Spectrum of peripheral neuropathies associated with surgical interventions; A neurophysiological assessment - Saidha, Shiv; Spillane, Jennifer; Mullins, Gerard; McNamara, Brian (Journal of Brachial Plexus and Peripheral Nerve Injury, 2010)
Background We hypothesized that a wide range of surgical procedures may be complicated by neuropathies, not just in close proximity but also remote from procedural sites. The aim of this study was to classify post-operative neuropathies and the procedures associated with them.Methods We retrospectively identified 66 patients diagnosed with post-procedure neuropathies between January 2005 and June 2008. We reviewed their referral cards and medical records for patient demographics, information on procedures, symptoms, as well as clinical and neurophysiological findings.Results Thirty patients (45.4%) had neuropathies remote from procedural sites and 36 patients (54.5%) had neuropathies in close proximity to procedural sites. Half of the remote neuropathies (15/30) developed following relatively short procedures. In 27% of cases (8/30) remote neuropathies were bilateral. Seven patients developed neuropathies remote from operative sites following hip arthroplasties (7/30: 23.3%), making hip arthroplasty the most common procedure associated with remote neuropathies.Sciatic neuropathies due to hip arthroplasty (12/36, 33.3%) accounted for the majority of neuropathies occurring in close proximity to operative sites.Five medial cutaneous nerve of forearm neuropathies occurred following arterio-venous fistula (AVF) formation.Conclusions An array of surgical procedures may be complicated by neuropathy. Almost half of post-procedure neuropathies occur remote from the site of procedure, emphasizing the need to try to prevent not just local, but also remote neuropathies. Mechanical factors and patient positioning should be considered in the prevention of post-operative neuropathies. There is a possible association between AVF formation and medial cutaneous nerve of forearm neuropathy, which requires further study for validation.